Low-density lipoprotein receptor-related protein 1 (LRP1) mediates neuronal Abeta42 uptake and lysosomal trafficking. - Rodrigo A Fuentealba; Qiang Liu; Juan Zhang; Takahisa Kanekiyo; Xiaoyan Hu; Jin-Moo Lee; Mary Jo LaDu; Guojun Bu (PLoS ONE)
Background Alzheimer's disease (AD) is characterized by the presence of early intraneuronal deposits of amyloid-beta 42 (Abeta42) that precede extracellular amyloid deposition in vulnerable brain regions. It has been hypothesized that endosomal/lysosomal dysfunction might be associated with the pathological accumulation of intracellular Abeta42 in the brain. Our previous findings suggest that the LDL receptor-related protein 1 (LRP1), a major receptor for apolipoprotein E, facilitates intraneuronal Abeta42 accumulation in mouse brain. However, direct evidence of neuronal endocytosis of Abeta42 through LRP1 is lacking. Methodology/principal findings Here we show that LRP1 endocytic function is required for neuronal Abeta42 uptake. Overexpression of a functional LRP1 minireceptor, mLRP4, increases Abeta42 uptake and accumulation in neuronal lysosomes. Conversely, knockdown of LRP1 expression significantly decreases neuronal Abeta42 uptake. Disruptions of LRP1 endocytic function by either clathrin knockdown or by removal of its cytoplasmic tail decreased both uptake and accumulation of Abeta42 in neurons. Finally, we show that LRP1-mediated neuronal accumulation of Abeta42 is associated with increased cellular toxicity. Conclusions/significance These results demonstrate that LRP1 endocytic function plays an important role in the uptake and accumulation of Abeta42 in neuronal lysosomes. These findings emphasize the central function of LRP1 in neuronal Abeta metabolism.